2014
DOI: 10.1021/jp503229u
|View full text |Cite
|
Sign up to set email alerts
|

Changing Weak Halogen Bonds into Strong Ones through Cooperativity with Beryllium Bonds

Abstract: The mutual interaction between beryllium bonds and halogen bonds within H2Be···FCl···Base complexes, where Base includes a wide set of N- and O-containing Lewis bases, has been studied at the M06-2X/6-31+G(d,p) level of theory. The reliability of this theoretical model was assessed by comparison with ab initio CCSD/aug-cc-pVTZ reference calculations. Cooperative effects were investigated within the framework of the atoms in molecules theory (AIM) by analyzing the topology of the electron density and the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…Spin-spin coupling constants were evaluated using the equation-of-motion coupled cluster singles and doubles (EOM-CCSD) method in the CI(configuration interaction)-like approximation, 42,43 with all electrons correlated. For these calculations, the Ahlrichs 44 qzp basis set was placed on 13 C, 15 N, and 19 F, and the qz2p basis set on 35 Cl. A basis set for 9 Be was developed using the same approach as used previously for 7 Li and 11 B.…”
Section: Methodsmentioning
confidence: 99%
“…Spin-spin coupling constants were evaluated using the equation-of-motion coupled cluster singles and doubles (EOM-CCSD) method in the CI(configuration interaction)-like approximation, 42,43 with all electrons correlated. For these calculations, the Ahlrichs 44 qzp basis set was placed on 13 C, 15 N, and 19 F, and the qz2p basis set on 35 Cl. A basis set for 9 Be was developed using the same approach as used previously for 7 Li and 11 B.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, these interactions have been widely investigated. [1][2][3][4][5] Recently,avariety of speciesi nw hich as ingle, simple Lewisb ase molecule (B, such as CO, N 2 ,H 2 O, H 2 S, C 2 H 2 ,orC 2 H 4 )coordinates to aneutral coinage metal diatomic MÀX( i.e. B···MÀX, in which Mi sC u, Ag, or Au;Xi sahalogen atom) have been investigated widely both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…They found that significant charge was transferred from the lone-pair donors (HF,H 2 O) to AuOH upon complex formation,s imilart ot hat in hydrogenbondedc omplexes.A dditionally,t wo simple complexes, H 2 O···AgÀCl and H 2 S···AgÀCl, were experimentally characterized by Legon et al [12] Considering the corresponding hydrogenbondeds ystems, they suggested that there was as ilver bond, analogoust ot he more familiarh ydrogen bond. Soon afterwards, [19] our computational studies on H 2 O···AgÀCl and H 2 S···AgÀCl showed that hyperconjugation interactions participated in Ag bonding. This was similart ot hat of hydrogenbondedc omplexes,i nw hich charget ransfer also occurred throughh yperconjugation interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual influence between beryllium bonds and other non-covalent bonds has also been investigated in recent years [105][106][107], though not as extensively as the preceding interactions. Mó et al carried out investigations on the effect of beryllium bonds on inter-and intra-hydrogen bonds [107].…”
Section: Interplay Between Non-covalent Interactionsmentioning
confidence: 99%